Suppressive activity of macrolide antibiotics on nitric oxide production by lipopolysaccharide stimulation in mice - Hajime Terao; Kazuhito Asano; Ken-ichi Kanai; Yoshiyuki Kyo; So Watanabe; Tadashi Hisamitsu; Harumi Suzaki (Mediators of Inflammation)
Background and aim: Low-dose and long-term administration of macrolide antibiotics into patients with chronic airway inflammatory diseases could favorably modify their clinical conditions. However, the therapeutic mode of action of macrolides is not well understood. Free oxygen radicals, including nitric oxide (NO), are well recognized as the important final effector molecules in the development and the maintenance of inflammatory diseases.